Outdoor Elderly Tracking System Using Line Tracking Mobile Robot with Bluetooth Communication System - A. A. Mukred, Jameel; A. Rahim, Ruzairi; Jian Bin, Phang; Abdullah, Qazwan; Alduais, N.A.M.; Al-Fadhali, Najib; Y.I, Adel (Evolution in Electrical and Electronic Engineering, 2020)
The concept of Smart City provides technology that assist the elderly to practice their normal life indoor, while this research will assist the elderly in the outdoor environment. This research presenting a method for tracking people at outdoor using mobile robot which will be given an outermost path (line tracking) in an enclosed outdoor area. The mobile robot uses 2 IR sensors to detect the designated path and the processor will instruct to control its motion; besides, the mobile robot also consists of the Bluetooth devices in order to detect the tracker device; so that the mobile robot will stop and produce sound when the Bluetooth tracker device is in range. The outdoor tracking mobile robot was designed and developed to detect the presence of the tracker device and provide signal to declare its presence to the user. The design of the mobile robot can be improved further in future so that it can detect the tracker device without using line tracking as well as it can maneuver on an irregular environment.